Effect of Biofertilizer, Microalgae and Nigella sativa on Purple Blotch (Alternaria porri) of Onion - Pooja Sanjay Hapase; Sobita Simon; Atul Suresh Bawane; Shubham Singh (Archives of Current Research International, 2025)
Onion (Allium cepa L.) is a biennial bulb crop produced all over the world. It is attacked by many diseases, out of which purple blotch of onion caused by Alternaria porri is the major disease. It causes heavy yield loss in both bulb production and seed production. The experiment was conducted to evaluate the effect of Biofertilizer, Microalgae and Nigella sativa on Purple blotch (Alternaria porri) of Onion. The results revealed that minimum disease incidence was observed at 45 and 60 days after transplanting in T7 Carbendazim (8.72%, 5.72%), followed by T6 Rhizobium + Azotobacter + Nigella sativa + Microalgae (21.47%, 16.88%), T4 Microalgae (23.54%, 17.21%) and maximum in T3 Nigella sativa (31.45%, 21.75%). The maximum plant height (cm) at 45 and 60 days after transplanting was observed in T6 Rhizobium + Azotobacter + Nigella sativa + Microalgae (45.21cm, 57.73cm), followed by T4 Microalgae (45.03cm, 57.46cm) and least in T3 Nigella sativa (36.23cm, 51.36cm). The maximum length of leaves (cm) at 45 and 60 days after transplanting was observed in T6 Rhizobium + Azotobacter + Nigella sativa + Microalgae (45.21cm, 61.28cm), followed by T4 Microalgae (45.03cm, 60.65cm) and least in T3 Nigella sativa (36.23cm, 52.70cm). The maximum bulb weight (gm) and bulb size (cm) was observed in T6 Rhizobium + Azotobacter + Nigella sativa + Microalgae (67.25gm, 6.76cm), followed by T4 Microalgae (64.30gm, 6.30cm) and least in T3 Nigella sativa (54.39gm, 4.45cm).